Optimalisasi Hak Kekayaan Intelektual dan Hilirisasi Inovasi Pembelajaran melalui Generative Artificial Intelligence - Odi Nurdiawan; Dadang Sudrajat; Rudi Kurniawan; Bani Nurhakim (Forum Kerjasama Pendidikan Tinggi, 2026)
The digital transformation of education requires teachers to possess digital literacy competencies, the ability to utilize Generative Artificial Intelligence (Generative AI), and an understanding of Intellectual Property Rights (IPR) protection regarding instructional innovations. However, a needs analysis conducted among teachers within the West Java Provincial Education Office Branch (Region X) revealed that the use of Generative AI in the learning process remains limited, understanding of IPR is inadequate, and efforts to commercialize or scale up (downstream) instructional innovations have not been optimally implemented. These conditions potentially hinder the creation of value-added and sustainable instructional innovations. This community service activity aims to optimize teachers' competencies in utilizing Generative AI to produce instructional innovations that are protected by IPR and possess potential for downstream application. The proposed solution was implemented in four stages: participant needs analysis; a workshop on digital literacy and Generative AI utilization; mentoring on IPR documentation and innovation downstreaming strategies; and evaluation using a Likert-scale questionnaire. The results indicate that participants were able to implement Generative AI to develop teaching materials, digital learning media, assessment instruments, and school administrative tools more effectively and innovatively. Evaluation of the activity showed that all indicators fell into the